Hubungan ibu hamil dengan Obesitas Dengan Kejadian Pre-Eklamsi Di Kecamatan Kaliwates Kabupaten Jember - Wieminaty, SST., M.Kes, Aldi Febrian (MEDICAL JURNAL OF AL-QODIRI, 2020)
Jember Regency is the 2nd (second) highest place in the Maternal Mortality Rate at East Java. There was an increase number of maternal deaths from 2014 to 2017 at Jember Regency. The trias ocauses maternal of death included bleeding (28%), preeclampsia / eclampsia (24%), and infection (11%). Obesity triggers the incidence of preeclampsia through several mechanisms, namely superimposed preeclampsia, or through metabolite triggers and other micro molecules. The purpose of this study was to analyze the relationship between pregnant women who obesity with the incidence of preeclampsia. This type of research is descriptive with quantitative analysis and the research uses a cross-sectional approach. The population of this study were 182 pregnant women in the Kaliwates district, Jember in May-August. above 34 weeks pregnant mom, and the exclusion criteria were mothers who were not willing to be respondents. The results obtained were 66 pregnant women, this study used the Chi-Square test. The results of this study can be concluded that there is a relationship between pregnant women and obesity to the incidence of preeclampsia, namely as much as 70.0%, and pregnant women with obesity who do not experience preeclampsia as much as 30.0%. From the statistical test, the results of the null hypothesis are rejected with a P value of 0.000 <0.05, which means that there is a relationship or there is a relationship between pregnant women and obesity with the incidence of preeclampsia. Keywords: pregnant woman, obesity, preeclampsia